Pemberdayaan Kelompok Wanita Tani Bawang Merah sebagai Upaya Peningkatan Kesejahteraan Keluarga - Retno Indah Hernawati; Natalistyo (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Tarubatang Village is one of the shallots producing centers in Central Java. When the main harvest season arrives, the supply of shallots becomes abundant and causes shallot prices to fall. The existence of the Sumber Rejeki Women Farmers Group (KWT) is an alternative to improve people's welfare, through further processing shallots into fried shallots. Even though the production process is still incidental, this activity needs to be managed properly. In determining the cost of products, there were still errors in the calculations, so that the impact on profit information was greater than it really was. Some factory overhead costs are not calculated. With this training, it is hoped that KWT Sumber Rejeki can review the calculation of the cost of its products.